A magnetic self-migration anti-rust mortar steel bar and preparation method thereof

By using magnetic self-migration technology of iron cobaltate particles and zeolite-loaded rust inhibitors in reinforced concrete structures, the problem of difficulty in migrating traditional rust inhibitors to the surface of the steel bars is solved, and directional uniform migration and efficient rust inhibition are achieved.

CN116621486BActive Publication Date: 2025-04-25NANJING HYDRAULIC RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310659260.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-06
Publication Date
2025-04-25
Estimated Expiration
2043-06-06

AI Technical Summary

Technical Problem

In traditional reinforced concrete structures, it is difficult for rust inhibitors to migrate spontaneously to the surface of the steel bars, resulting in waste and environmental pollution, while the migration direction is uncertain.

Method used

Iron cobaltate particles are used as the magnetic power source, and the zeolite-loaded rust inhibitor is grown on the surface of iron cobaltate particles through the static method to form magnetic rust resist materials, and are "transported" to the surface of the steel bars in a direction and even manner.

Benefits of technology

It effectively solves the problems of migration difficulties and uncertain migration direction of rust inhibitors, improves the rust resistance effect, and reduces the waste of rust inhibitors and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116621486B_ABST
    Figure CN116621486B_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic self-migrating rust-proof mortar steel bar and a preparation method thereof, which belongs to the field of steel bar rust inhibitors, with iron cobaltate particles as the source of magnetic power, and zeolite as a direct sustained-release connector between iron cobaltate and the rust inhibitor. A static method is adopted to make the zeolite-loaded rust inhibitor grow on the surface of the iron cobaltate particles, so as to obtain a magnetic rust-proof material, iron cobaltate-zeolite-rust inhibitor. The iron cobaltate-zeolite-rust inhibitor is added into the mortar and applied to the surface of the steel bar. With the help of the magnetism of the iron cobaltate particles, the zeolite-loaded rust inhibitor can be "transported" to the surface of the steel bar in a direction and uniform manner, effectively solving the problem of the difficulty of rust inhibitor migration and the uncertainty of migration direction, and greatly improving the use efficiency, economy and environmental protection of the rust inhibitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of steel bar rust inhibitors, and in particular to magnetic self-migration rust-proof mortar steel bars and a preparation method thereof. Background Art

[0002] Reinforced concrete structures are widely used in various projects. They have the characteristics of high strength, long service life and good economy. However, the steel corrosion problem caused by chloride ion erosion is an important factor restricting the long-term safe service of reinforced concrete structures. Common treatment measures include special steel bars, concrete coatings, cathodic protection and adding steel bar rust inhibitors.

[0003] Adding rust inhibitors is a common rust prevention method, and there has been a lot of research and application at home and abroad. However, traditional rust inhibitors have some obvious shortcomings. First, the rust inhibitors added to concrete are evenly dispersed in the concrete, and most of the rust inhibitors are difficult to automatically migrate to the surface of the steel bars, resulting in a large amount of waste of rust inhibitors. Secondly, the migration direction of the rust inhibitor in concrete is uncertain. Some rust inhibitors will migrate toward the surface of the concrete and eventually leak into the environment, causing pollution. Therefore, it is urgent to improve the directional migration ability of rust inhibitors in cement-based materials. Summary of the invention

[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide a magnetic self-migrating rust-resistant mortar steel bar, using cobalt iron particles as the source of magnetic power, using a static method to grow a zeolite-loaded rust inhibitor on the surface of the cobalt iron particles, and obtaining a magnetic rust-resistant material cobalt iron-zeolite-rust inhibitor, and then adding the cobalt iron-zeolite-rust inhibitor into the mortar and applying it to the surface of the steel bar. With the help of the magnetism of the cobalt iron particles, the zeolite-loaded rust inhibitor in the mortar layer can be "transported" to the surface of the steel bar in a directional and uniform manner, effectively solving the problem of difficult migration of the rust inhibitor and uncertain migration direction.

[0005] In order to achieve the above object, the present invention adopts the following technical solution: a magnetic self-migration anti-rust mortar steel bar and a preparation method thereof, comprising the following steps:

[0006] Step (1) Preparation of iron cobaltate-zeolite-rust inhibitor:

[0007] First, prepare a sodium hydroxide solution, then add silicic acid, hexamethyleneimine, sodium aluminate solution, iron cobaltate particles and rust inhibitor into the sodium hydroxide solution in sequence, and stir thoroughly to form a mixed solution; after the whole is stirred at a constant temperature of 60°C for 5 to 60 minutes, it is transferred to a reaction kettle, sealed, and placed in a 120 to 180°C oven for crystallization for 24 to 96 hours; after the synthesis is completed, the precipitate is washed to neutrality, and after baking at 60°C for 24 hours, the iron cobaltate-zeolite-rust inhibitor is obtained.

[0008] Step (2) Preparation of magnetic self-migration anti-rust mortar:

[0009] The iron cobaltate-zeolite-rust inhibitor particles are evenly dispersed in the mortar, wherein a water reducer and a retarder are also added to the mortar. The mortar is then used as a steel bar protective layer and applied to the steel bar surface to prepare a magnetic self-migration rust-resistant mortar steel bar.

[0010] Furthermore, in step (1), the particle size of the iron cobaltate particles is about 80 nm.

[0011] Furthermore, in step (1), the rust inhibitor is triethanolamine, benzotriazole or sodium molybdate.

[0012] Furthermore, in step (1), when preparing the iron cobaltate-zeolite-rust inhibitor, the concentrations of the various components (relative to the mass concentration of deionized water) are respectively:

[0013] Sodium hydroxide: 0.5%~1%;

[0014] Silicic acid: 15% to 30%;

[0015] Hexamethyleneimine: 15% to 30%;

[0016] Iron cobaltate particles: 0.3% to 1%;

[0017] Rust inhibitor: 1% to 3%;

[0018] Sodium aluminate solution: 75-150%, wherein the mass concentration of the sodium aluminate solution itself is 2%;

[0019] Furthermore, in step (2), the water-cement ratio of the mortar is 0.45-0.55, the mortar-binder ratio is 0.35-0.45, and the amount of the cobalt iron-zeolite-rust inhibitor is 3%-6% of the mass of the cement;

[0020] Furthermore, in step (2), the water reducing agent added to the mortar is a polycarboxylate water reducing agent, and the retarder is sodium gluconate, and the amounts of the two are 0.05% to 0.15% and 0.03% to 0.1% respectively relative to the mass of cement.

[0021] Furthermore, in step (2), the thickness of the magnetic self-migration rust-proof mortar on the surface of the steel bar is 1 to 5 mm;

[0022] Furthermore, in step (2), the curing temperature of the steel mortar is 25° C., the curing humidity is 95%, and the curing time is 72 hours.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. To address the problem of the difficulty of spontaneous migration of rust inhibitors in cement-based materials, the present invention combines cobalt iron particles with zeolite-loaded rust inhibitors through a static method. With the help of the centripetal magnetic force of the cobalt iron particles surrounding the steel bars, the zeolite-loaded rust inhibitors can be "transported" to the vicinity of the steel bar surface, effectively solving the problem of the difficulty of spontaneous migration of rust inhibitors in cement-based materials.

[0025] 2. When the rust inhibitor is directly added to the cement-based material, the migration direction of the rust inhibitor is not fixed. A part of the rust inhibitor will migrate to the surface of the steel bar until it leaks into the environment, which pollutes the environment on the one hand and causes waste of the rust inhibitor on the other hand, increasing the economic cost. The present invention is based on the centripetal driving force around the steel bar provided by the cobalt ferromagnetic particles, so that all the rust inhibitors migrate centripetally around the steel bar in a consistent manner, effectively solving the problem of non-directional migration of the rust inhibitor in the cement-based material.

[0026] 3. Traditional rust inhibitors are mixed into the concrete structure as a whole, which results in a large amount of rust inhibitors actually added. The present invention, by taking advantage of the magnetic power migration, only needs to add the rust inhibitor into the mortar coating to exert an excellent rust-proof effect, greatly reducing the amount of rust inhibitors added. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a comparison chart of the anti-corrosion performance of the magnetic self-migration anti-rust mortar steel bars in this embodiment. DETAILED DESCRIPTION

[0028] In order to better explain the present invention, the technical solution of the present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It should be noted that all technical and scientific terms used in this embodiment have the same meanings as those commonly understood by ordinary technicians in the technical field to which the present invention belongs.

[0029] Example 1

[0030] (1) Preparation of iron cobaltate-zeolite-rust inhibitor:

[0031] The specific synthesis method of cobalt acid iron-zeolite-rust inhibitor is as follows: first prepare sodium hydroxide solution; add silicate, hexamethyleneimine, sodium aluminate solution, cobalt acid iron particles and rust inhibitor triethanolamine to the sodium hydroxide solution in sequence. Among them, the mass concentration of sodium hydroxide is 0.5% of deionized water, the mass concentration of silicate is 15%, the mass concentration of hexamethyleneimine is 15%, the mass concentration of cobalt acid iron particles is 0.3% (the particle size of cobalt acid iron particles is about 80nm), the mass concentration of rust inhibitor is 1%, and the dosage of sodium aluminate solution is 75% of the mass of deionized water in the above solution, wherein the mass concentration of sodium aluminate solution itself is 2%. After fully stirring, a mixed solution is formed, and after the whole is stirred at a constant temperature of 60°C for 5 minutes, it is transferred to a reactor and sealed, and placed in a 120°C oven for crystallization for 24 hours; after the synthesis is completed, the precipitate is washed to neutrality, and after drying at 60°C for 24 hours, the cobalt acid iron-zeolite-rust inhibitor is obtained.

[0032] (2) Preparation of magnetic self-migration anti-rust mortar:

[0033] The iron cobaltate-zeolite-rust inhibitor particles are evenly dispersed in the mortar, and the dosage is 3% of the cement mass. The water-cement ratio of the mortar is 0.45, and the mortar-brick ratio is 0.35. Among them, polycarboxylic acid water reducer and sodium gluconate retarder are also added to the mortar, and the dosages of the two relative to the cement mass are 0.05% and 0.03%, respectively. The mortar is used as a steel bar protective layer and is applied to the surface of the steel bar. The mortar layer has a thickness of 1mm. Then the steel bar-mortar is cured at a temperature of 25°C and a humidity of 95%. The curing time is 72 hours to prepare a magnetic self-migration rust-resistant mortar steel bar.

[0034] Example 2

[0035] (1) Preparation of iron cobaltate-zeolite-rust inhibitor:

[0036] The specific synthesis method of cobalt iron-zeolite-rust inhibitor is as follows: first prepare sodium hydroxide solution; add silicate, hexamethyleneimine, sodium aluminate solution, cobalt iron particles and rust inhibitor triethanolamine to the sodium hydroxide solution in sequence. Among them, the mass concentration of sodium hydroxide is 0.75% of deionized water, the mass concentration of silicate is 18%, the mass concentration of hexamethyleneimine is 18%, the mass concentration of cobalt iron particles is 0.6% (the particle size of cobalt iron particles is about 80nm), the mass concentration of rust inhibitor is 2%, and the dosage of sodium aluminate solution is 110% of the mass of deionized water in the above solution, wherein the mass concentration of sodium aluminate solution itself is 2%. After fully stirring, a mixed solution is formed, and after the whole is stirred at a constant temperature of 60°C for 30 minutes, it is transferred to a reactor and sealed, and placed in a 150°C oven for crystallization for 60 hours; after the synthesis is completed, the precipitate is washed to neutrality, and after drying at 60°C for 24 hours, the cobalt iron-zeolite-rust inhibitor is obtained.

[0037] (2) Preparation of magnetic self-migration anti-rust mortar:

[0038] The iron cobaltate-zeolite-rust inhibitor particles are evenly dispersed in the mortar, and the dosage is 4.5% of the cement mass. The water-cement ratio of the mortar is 0.5, and the mortar-brick ratio is 0.4. Among them, polycarboxylic acid water reducer and sodium gluconate retarder are also added to the mortar, and the dosages of the two relative to the cement mass are 0.1% and 0.06%, respectively. The mortar is used as a steel bar protective layer and is applied to the surface of the steel bar. The thickness of the mortar layer is 3mm. Then the steel bar-mortar is cured at a temperature of 25°C and a humidity of 95%. The curing time is 72 hours to prepare a magnetic self-migration rust-resistant mortar steel bar.

[0039] Example 3

[0040] (1) Preparation of iron cobaltate-zeolite-rust inhibitor:

[0041] The specific synthesis method of cobalt iron-zeolite-rust inhibitor is as follows: first prepare sodium hydroxide solution; add silicate, hexamethyleneimine, sodium aluminate solution, cobalt iron particles and rust inhibitor benzotriazole to the sodium hydroxide solution in sequence. Among them, the mass concentration of sodium hydroxide is 1% of deionized water, the mass concentration of silicate is 30%, the mass concentration of hexamethyleneimine is 30%, the mass concentration of cobalt iron particles is 1% (the particle size of cobalt iron particles is about 80nm), the mass concentration of rust inhibitor is 3%, and the dosage of sodium aluminate solution is 150% of the mass of deionized water in the above solution, wherein the mass concentration of sodium aluminate solution itself is 2%. After fully stirring, a mixed solution is formed, and after the whole is stirred at a constant temperature of 60°C for 60min, it is transferred to a reactor and sealed, and placed in a 180°C oven for crystallization for 96h; after the synthesis is completed, the precipitate is washed to neutrality, and after drying at 60°C for 24h, the cobalt iron-zeolite-rust inhibitor is obtained.

[0042] (2) Preparation of magnetic self-migration anti-rust mortar:

[0043] The iron cobaltate-zeolite-rust inhibitor particles are evenly dispersed in the mortar, and the dosage is 6% of the cement mass. The water-cement ratio of the mortar is 0.55, and the mortar-brick ratio is 0.45. Among them, polycarboxylic acid water reducer and sodium gluconate retarder are also added to the mortar, and the dosages of the two relative to the cement mass are 0.15% and 0.1% respectively. The mortar is used as a steel bar protective layer and is applied to the surface of the steel bar. The thickness of the mortar layer is 5mm. Then the steel bar-mortar is cured at a temperature of 25°C and a humidity of 95%. The curing time is 72 hours to prepare a magnetic self-migration rust-resistant mortar steel bar.

[0044] Example 4

[0045] (1) Preparation of iron cobaltate-zeolite-rust inhibitor:

[0046] The specific synthesis method of cobalt acid iron-zeolite-rust inhibitor is as follows: first prepare sodium hydroxide solution; add silicate, hexamethyleneimine, sodium aluminate solution, cobalt acid iron particles and rust inhibitor benzotriazole to the sodium hydroxide solution in sequence. Among them, the mass concentration of sodium hydroxide is 1% of deionized water, the mass concentration of silicate is 25%, the mass concentration of hexamethyleneimine is 20%, the mass concentration of cobalt acid iron particles is 0.6% (the particle size of cobalt acid iron particles is about 80nm), the mass concentration of rust inhibitor is 2%, and the dosage of sodium aluminate solution is 75% of the mass of deionized water in the above solution, wherein the mass concentration of sodium aluminate solution itself is 2%. After fully stirring, a mixed solution is formed, and after the whole is stirred at a constant temperature of 60°C for 5 minutes, it is transferred to a reactor and sealed, and placed in a 150°C oven for crystallization for 48 hours; after the synthesis is completed, the precipitate is washed to neutrality, and after drying at 60°C for 24 hours, the cobalt acid iron-zeolite-rust inhibitor is obtained.

[0047] (2) Preparation of magnetic self-migration anti-rust mortar:

[0048] The iron cobaltate-zeolite-rust inhibitor particles are evenly dispersed in the mortar, and the dosage is 3% of the cement mass. The water-cement ratio of the mortar is 0.50, and the mortar-brick ratio is 0.40. Among them, polycarboxylic acid water reducer and sodium gluconate retarder are also added to the mortar, and the dosages of the two relative to the cement mass are 0.1% and 0.06%, respectively. The mortar is used as a steel bar protective layer and is applied to the surface of the steel bar. The thickness of the mortar layer is 3mm. Then the steel bar-mortar is cured at a temperature of 25°C and a humidity of 95%. The curing time is 72 hours to prepare a magnetic self-migration rust-resistant mortar steel bar.

[0049] Example 5

[0050] (1) Preparation of iron cobaltate-zeolite-rust inhibitor:

[0051] The specific synthesis method of cobalt iron-zeolite-rust inhibitor is as follows: first prepare sodium hydroxide solution; add silicate, hexamethyleneimine, sodium aluminate solution, cobalt iron particles and rust inhibitor sodium molybdate to the sodium hydroxide solution in sequence. Among them, the mass concentration of sodium hydroxide is 0.5% of deionized water, the mass concentration of silicate is 15%, the mass concentration of hexamethyleneimine is 22%, the mass concentration of cobalt iron particles is 0.6% (the particle size of cobalt iron particles is about 80nm), the mass concentration of rust inhibitor is 3%, and the dosage of sodium aluminate solution is 150% of the mass of deionized water in the above solution, wherein the mass concentration of sodium aluminate solution itself is 2%. After fully stirring, a mixed solution is formed, and after the whole is stirred at a constant temperature of 60°C for 60min, it is transferred to a reactor and sealed, and placed in a 150°C oven for crystallization for 60h; after the synthesis is completed, the precipitate is washed to neutrality, and after drying at 60°C for 24h, the cobalt iron-zeolite-rust inhibitor is obtained.

[0052] (2) Preparation of magnetic self-migration anti-rust mortar:

[0053] The iron cobaltate-zeolite-rust inhibitor particles are evenly dispersed in the mortar, and the dosage is 4.5% of the cement mass. The water-cement ratio of the mortar is 0.5, and the mortar-brick ratio is 0.4. Among them, polycarboxylic acid water reducer and sodium gluconate retarder are also added to the mortar, and the dosages of the two relative to the cement mass are 0.1% and 0.06%, respectively. The mortar is used as a steel bar protective layer and is applied to the surface of the steel bar. The thickness of the mortar layer is 5mm. Then the steel bar-mortar is cured at a temperature of 25°C and a humidity of 95%. The curing time is 72 hours to prepare a magnetic self-migration rust-resistant mortar steel bar.

[0054] Example 6

[0055] (1) Preparation of iron cobaltate-zeolite-rust inhibitor:

[0056] The specific synthesis method of cobalt iron-zeolite-rust inhibitor is as follows: first prepare sodium hydroxide solution; add silicate, hexamethyleneimine, sodium aluminate solution, cobalt iron particles and rust inhibitor sodium molybdate to the sodium hydroxide solution in sequence. Among them, the mass concentration of sodium hydroxide is 0.5% of deionized water, the mass concentration of silicate is 30%, the mass concentration of hexamethyleneimine is 15%, the mass concentration of cobalt iron particles is 0.3% (the particle size of cobalt iron particles is about 80nm), the mass concentration of rust inhibitor is 1%, and the dosage of sodium aluminate solution is 150% of the mass of deionized water in the above solution, wherein the mass concentration of sodium aluminate solution itself is 2%. After fully stirring, a mixed solution is formed, and after the whole is stirred at a constant temperature of 60°C for 60 minutes, it is transferred to a reactor and sealed, and placed in a 150°C oven for crystallization for 96 hours; after the synthesis is completed, the precipitate is washed to neutrality, and after drying at 60°C for 24 hours, the cobalt iron-zeolite-rust inhibitor is obtained.

[0057] (2) Preparation of magnetic self-migration anti-rust mortar:

[0058] The iron cobaltate-zeolite-rust inhibitor particles are evenly dispersed in the mortar, and the dosage is 6% of the cement mass. The water-cement ratio of the mortar is 0.50, and the mortar-brick ratio is 0.45. Among them, polycarboxylic acid water reducer and sodium gluconate retarder are also added to the mortar, and the dosages of the two relative to the cement mass are 0.1% and 0.06%, respectively. The mortar is used as a steel bar protective layer and is applied to the surface of the steel bar. The thickness of the mortar layer is 5mm. Then the steel bar-mortar is cured at a temperature of 25°C and a humidity of 95%. The curing time is 72 hours to prepare a magnetic self-migration rust-resistant mortar steel bar.

[0059] Comparative Example 1

[0060] Rust-resistant mortar steel bars were prepared according to the method in step (2) of Example 1, but without adding iron cobaltate-zeolite-rust inhibitor particles.

[0061] Comparative Example 2

[0062] Rust-resistant mortar steel bars were prepared according to the method in step (2) of Example 5, but without adding iron cobaltate-zeolite-rust inhibitor particles.

[0063] Table 1 Open circuit potential

[0064]

[0065] Evaluation of rust resistance performance:

[0066] The anti-corrosion performance of the magnetic self-migration rust-proof mortar steel bar prepared in this embodiment was evaluated in a corrosive environment of 4% mass concentration NaCl solution. The anti-corrosion performance of the magnetic self-migration rust-proof mortar steel bar after being immersed in the corrosive solution for different time periods was tested by electrochemical means. From the open circuit potential data and Figure 1 It can be seen from the rust-proof efficiency data that the anti-corrosion performance of the magnetic self-migration rust-proof mortar steel bars proposed in this embodiment is significantly better than that of ordinary mortar steel bars. This is mainly due to the magnetic effect of the iron cobalt oxide particles, which can "transport" the zeolite-loaded rust inhibitor to the steel bar surface in a directional and uniform manner, effectively solving the problem of difficult migration of the rust inhibitor and uncertain migration direction, and greatly improving the rust-proof effect.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing magnetic self-migration anti-rust mortar steel bars for reinforced concrete corrosion protection, characterized in that: Zeolite is used as a carrier of the rust inhibitor, and iron cobaltate particles are used as a power source for magnetic migration. Zeolite-loaded rust inhibitor is grown on the surface of iron cobaltate by a static method and used in a steel mortar protective layer. The method specifically includes the following steps: (1) Preparation of iron cobaltate-zeolite-rust inhibitor: First, a sodium hydroxide solution is prepared, and then silicate, hexamethyleneimine, sodium aluminate solution, iron cobaltate particles and a rust inhibitor are added to the sodium hydroxide solution in sequence, and the mixture is fully stirred to form a mixed solution; the mixed solution is stirred at a constant temperature of 60° C. for 5 to 60 minutes, and then transferred to a reaction kettle, sealed, and placed in a 120 to 180° C. oven for crystallization for 24 to 96 hours; after the synthesis is completed, the precipitate is washed to neutrality, and after baking at 60° C. for 24 hours, the iron cobaltate-zeolite-rust inhibitor is obtained; (2) Preparation of magnetic self-migration anti-rust mortar steel bars: The iron cobaltate-zeolite-rust inhibitor particles are evenly dispersed in the mortar, wherein a water reducer and a retarder are added to the mortar; the mortar is then used as a steel bar protective layer and applied to the surface of the steel bar, and then the steel bar-mortar is cured to prepare a magnetic self-migration rust-resistant mortar steel bar.

2. The method for preparing a magnetic self-migration anti-rust mortar steel bar according to claim 1, characterized in that: In the step (1), the particle size of the iron cobaltate particles is 80 nm.

3. The method for preparing a magnetic self-migration anti-rust mortar steel bar according to claim 1, characterized in that: In the step (1), the rust inhibitor is triethanolamine, benzotriazole or sodium molybdate.

4. The method for preparing a magnetic self-migration anti-rust mortar steel bar according to claim 1, characterized in that: In the step (1), when preparing the iron cobaltate-zeolite-rust inhibitor, the concentrations of the various components are respectively: Sodium hydroxide: 0.5%~1%; Silicic acid: 15% to 30%; Hexamethyleneimine: 15% to 30%; Iron cobaltate particles: 0.3% to 1%; Rust inhibitor: 1% to 3%; Sodium aluminate solution: 75-150%, wherein the mass concentration of the sodium aluminate solution itself is 2%.

5. The method for preparing a magnetic self-migration anti-rust mortar steel bar according to claim 1, characterized in that: In the step (2), the water-cement ratio of the mortar is 0.45-0.55, the mortar-brick ratio is 0.35-0.45, and the amount of the iron cobaltate-zeolite-rust inhibitor is 3%-6% of the mass of the cement.

6. The method for preparing a magnetic self-migration anti-rust mortar steel bar according to claim 1, characterized in that: In the step (2), the water reducing agent added to the mortar is a polycarboxylate water reducing agent, and the retarder is sodium gluconate, and the amounts of the two are 0.05% to 0.15% and 0.03% to 0.1% respectively relative to the mass of cement.

7. The method for preparing a magnetic self-migration anti-rust mortar steel bar according to claim 1, characterized in that: In the step (2), the thickness of the magnetic migration anti-rust mortar on the surface of the steel bar is 1 to 5 mm.

8. The method for preparing a magnetic self-migration anti-rust mortar steel bar according to claim 1, characterized in that: In the step (2), the curing temperature of the steel bar-mortar is 25° C., the curing humidity is 95%, and the curing time is 72 hours.

Citation Information

Patent Citations

  • Imidazole derivative, and preparation method and application thereof as reinforced concrete corrosion inhibitor

    CN111116482A

  • Multifunctional admixture for inhibiting chloride ion diffusion and steel bar corrosion in concrete and preparation method of multifunctional admixture

    CN113248167A